Control of the pattern-recognition receptor EFR by an ER protein complex in plant immunity - Nekrasov, Vladimir; Li, Jing; Batoux, Martine; Roux, Milena; Chu, Zhao-Hui; Lacombe, Severine; Rougon, Alejandra; Bittel, Pascal; Kiss-Papp, Marta; Chinchilla, Delphine; van Esse, H Peter; Jorda, Lucia; et al. (The EMBO journal, 2009)
In plant innate immunity, the surface‐exposed leucine‐rich repeat receptor kinases EFR and FLS2 mediate recognition of the bacterial pathogen‐associated molecular patterns EF‐Tu and flagellin, respectively. We identified the Arabidopsis stromal‐derived factor‐2 (SDF2) as being required for EFR function, and to a lesser extent FLS2 function. SDF2 resides in an endoplasmic reticulum (ER) protein complex with the Hsp40 ERdj3B and the Hsp70 BiP, which are components of the ER‐quality control (ER‐QC). Loss of SDF2 results in ER retention and degradation of EFR. The differential requirement for ER‐QC components by EFR and FLS2 could be linked to N‐glycosylation mediated by STT3a, a catalytic subunit of the oligosaccharyltransferase complex involved in co‐translational N‐glycosylation. Our results show that the plasma membrane EFR requires the ER complex SDF2–ERdj3B–BiP for its proper accumulation, and provide a demonstration of a physiological requirement for ER‐QC in transmembrane receptor function in plants. They also provide an unexpected differential requirement for ER‐QC and N‐glycosylation components by two closely related receptors.